Self-care can be an alternative to expand access to universal health care: What policy makers, governments and implementers can consider for South Africa - Nyatela, Athini; Nqakala, Sizwe; Singh, Leanne; Johnson, Taylor; Gumede, Siphamandla (Frontiers in Reproductive Health, 2022)
As a result of collaboration amongst the various decision-makers in the field of healthcare, there has been an improvement in the access to healthcare and living conditions globally. Nonetheless, poorer communities continue to benefit the least from public investment. To bridge the gap, self-care can be a viable alternative as it allows individuals and communities to reduce their dependence on government healthcare solutions. Barriers to self-care do exist. Some of these are cost effectiveness, usability of self-care instruments, differentiated strategies and linkage to care. In identifying these obstacles, it is also worthwhile to investigate how they can be mitigated. To encourage sustained self-care in the HIV continuum, contextual factors as well as the manner in which individuals and communities engage with self-care must be considered. In South Africa, multiple variables come into play: literacy levels, cultural influences, socio-economic conditions and access to resources are some of these. Evidence demonstrates how self-care can be promoted by various stakeholders re-strategising to tweak and in some cases totally change existing structures. This paper explores some of the transformations, like at a governmental level where the supply of HIV self-testing kits is increased, at a production level where instructions for use are reformatting, in communities where sports programmes fulfil the dual purpose of developing sport skills and providing HIV education concurrently, and at an individual level where greater awareness invites greater participation in self-care. While self-care is a promising proposal, it is not a replacement for traditional health-care practices, but a complementary approach.